An integrated inverse numerical–experimental approach to determine the dynamic Mode-I interlaminar fracture toughness of fibre composites. (1st August 2022) - Ponnusami, Sathiskumar A.; Cui, Hao; Erice, Borja; Lißner, Maria; Pathan, Mehtab; Petrinic, Nik
Abstract: A combined numerical–experimental methodology is presented to determine the dynamic Mode-I fracture properties of Fibre-Reinforced Polymer (FRP) composites. The experimental aspect consists of a modified Wedge-Double cantilever Beam (WDCB) test using a Split Hopkinson Pressure Bar (SHPB) set-up followed by a numerical inverse modelling strategy using cohesive-zone approach. The proposed method is inherently robust due to the use of three independent comparison metrics namely, the strain–displacement response, the crack length history and the crack opening history to uniquely determine the delamination properties. More importantly, the complexity of dealing with the frictional effects between the wedge and the DCB specimen is effectively circumvented by utilising appropriate acquisition techniques. The proposed methodology is applied to extract the high-rate interlaminar fracture properties of a carbon fibre reinforced composite, IM7/8552 and it is further shown that a high level of confidence in the calibrated data can be established by adopting the proposed methodology.